Пошаговое объяснение:
0,3×(Х-4)-0,4×(6-5Х)=1,6
0,3x-1,2-2,4+2x = 1,6
2,3x = 1,6 + 1,2 + 2,4
2,3x = 5,2
(примерно, ибо там бесконечное число) x = 2,26
Ответ:
0,3(х-4)-0,4(6-5х)=1,6
0,3х-1,2-2,4-2х=1,6
0,3х-2х=1,6+1,2+2,4
х=5,2
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Пошаговое объяснение:
0,3×(Х-4)-0,4×(6-5Х)=1,6
0,3x-1,2-2,4+2x = 1,6
2,3x = 1,6 + 1,2 + 2,4
2,3x = 5,2
(примерно, ибо там бесконечное число) x = 2,26
Ответ:
0,3(х-4)-0,4(6-5х)=1,6
0,3х-1,2-2,4-2х=1,6
0,3х-2х=1,6+1,2+2,4
х=5,2